Star Fruit Intoxication in Chronic Kidney Disease: Our Experience - Shumy, Farzana; Ahmed, Mohiuddin; Anam, Ahmad Mursel; Polash, M Mufizul Islam; Islam, M Motiul; Nessa, Shahazadi Sayeeda Tun (Bangladesh Critical Care Journal, 2014)
We report a case, where a patient of chronic kidney disease developed hiccups and alteration of consciousness after consuming star fruit. Prompt recognition of his features lead to commencement of hemodialysis, and that saved his life. DOI: http://dx.doi.org/10.3329/bccj.v2i1.19968 Bangladesh Crit Care J March 2014; 2 (1): 40-41